ZC3H13-mediated N6-methyladenosine modification of PHF10 is impaired by fisetin which inhibits the DNA damage response in pancreatic cancer. (1st April 2022) - Huang, Chaojie; Zhou, Senhao; Zhang, Chaolei; Jin, Yifeng; Xu, Gao; Zhou, Liangjing; Ding, Guoping; Pang, Tianshu; Jia, Shengnan; Cao, Liping
Abstract: DNA damage repair is a major barrier for chemotherapy efficacy of pancreatic ductal adenocarcinoma (PDAC), including the efficacy of platinum-based and gemcitabine/nab-paclitaxel treatments. N6-methyladenosine modifications (m 6 A) have recently been reported to play a role in homologous recombination (HR) repair of DNA double strand breaks (DSBs); however, the mechanism of action remains unknown. Our previous work indicated that fisetin may be a promising anti-tumour agent that induces DNA damage. In this study, we reported that fisetin induced DSBs and suppressed HR repair through m 6 A modification in PDAC cells. The m 6 A writer ZC3H13 and PHF10, which is a subunit of the PBAF chromatin remodelling complex, were identified as the main molecules affected by fisetin treatment. To our knowledge, it's the first time that PHF10 was found and involved in the DNA damage response. PHF10 loss-of-function resulted in elevated recruitment of γH2AX, RAD51, and 53BP1 to DSB sites and decreased HR repair efficiency. Moreover, ZC3H13 knockdown downregulated the m 6 A methylation of PHF10 and decreased PHF10 translation in a YTHDF1-dependent manner. In conclusion, our study demonstrates that fisetin enhanced DSBs via ZC3Hl3-mediated m 6 A modification of PHF10, which may provide insight into novel therapeutic approaches for PDAC. Highlights: Fisetin induced DNA damage response through regulating m 6 A RNA methylation in pancreatic cancer cells. ZC3H13 regulates the translation of PHF10 mRNA in a YTHDF-1-dependent manner. PHF10 regulated the cellular response to DNA damage in PDAC cells.